A Passive Method for the Detection of Explosives and Weapons-Grade Plutonium in Nuclear Warheads. Issue 2 (2nd September 2018) - Meng, Huang; Jianyu, Zhu; Jun, Wu; Rui, Li
Abstract: Before a nuclear warhead is dismantled, the special nuclear material and explosives must be identified and authenticated. This paper proposes a passive method to detect and identify weapons-grade plutonium cores and explosives in nuclear warheads based on neutron analyses techniques. This paper first describes the principles of a passive detection method that calculates the element number ratio (namely the ratio between the nucleus numbers of two different elements) of the element of interest to identify a source and how this method could be applied to the detection of warhead explosives. Second, a simulation of weapons-grade plutonium using JMCT software is described. The simulation assumes the elemental components of the explosives are activated by the production and transport of neutrons from the weapons-grade plutonium core and counted the gamma ray emissions of from the resultant hydrogen, carbon, and nitrogen nuclides with a high-purity germanium detector (HPGe) array. After an hour of counting, the element number ratios of these elements in the simulation were reconstructed and accurately matched the values for the explosives in the warhead. These results suggest that the passive method can be used to identify the presence of weapons-grade plutonium in the warhead. In addition, the simulation showed that the passive method can also discriminate between the various types of explosives in warheads, providing important physical information for the verification process during dismantlement.